Leading with empathy : understanding the needs of today's workforce - Pallapa, Gautham (John Wiley & Sons, Inc., 2022)
"Empathy is the ability to emotionally understand what other people fee, see things from their viewpoint, and image yourself in their place. Feeling heard and understood is a human need. Everyone needs to feel understood. Empathy helps us get in touch with our feelings and vies us an emotional understanding of ourselves and others. When a leader can look at a fellow workforce member and put themselves in their shoes, understand the pain and stress they are undergoing, and value their happiness above their own, they are genuinely empathic. This title will provide the tools necessary for a leader to become an empathic"--